2020
DOI: 10.1177/1440783320927089
|View full text |Cite
|
Sign up to set email alerts
|

Managing labour market re-entry following maternity leave among women in the Australian higher education sector

Abstract: Paid maternity leave policy attracts considerable attention in Australia and internationally, not least because taking a maternity break and employment re-entry benefits economies, businesses and well-being. The literature on factors contributing to a positive relationship between paid employment, reproduction and caring is fragmented and continues to highlight the complexity of the matter. Drawing on qualitative interviews, and Williams’ theory of domesticity ideology and Pocock’s work/care regimes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Many women who have returned to work reported that they would have liked a longer maternity leave (Juengst et al 2019;Tohme and Abi-Habib 2022), and those employed in workplaces not supporting breastfeeding often use annual leave to stay longer with their children (Wolde et al 2021). After returning to work, most women work the same or more hours per day than before their leave (Nguyen et al 2022) and report tensions between work and care demands (Martins et al 2019;Gregory 2021;Parcsi and Curtin 2013): women who continue breastfeeding after returning to work are those who experience more family-to-work conflict and overload (Spitzmueller et al 2016). On the one hand, soon after returning to work, women emphasize the difficulty of accessing parttime positions, the lack of flexibility in the workplace, and the prevalence of a non-family-friendly occupational culture.…”
Section: Work-life Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Many women who have returned to work reported that they would have liked a longer maternity leave (Juengst et al 2019;Tohme and Abi-Habib 2022), and those employed in workplaces not supporting breastfeeding often use annual leave to stay longer with their children (Wolde et al 2021). After returning to work, most women work the same or more hours per day than before their leave (Nguyen et al 2022) and report tensions between work and care demands (Martins et al 2019;Gregory 2021;Parcsi and Curtin 2013): women who continue breastfeeding after returning to work are those who experience more family-to-work conflict and overload (Spitzmueller et al 2016). On the one hand, soon after returning to work, women emphasize the difficulty of accessing parttime positions, the lack of flexibility in the workplace, and the prevalence of a non-family-friendly occupational culture.…”
Section: Work-life Balancementioning
confidence: 99%
“…On the one hand, soon after returning to work, women emphasize the difficulty of accessing parttime positions, the lack of flexibility in the workplace, and the prevalence of a non-family-friendly occupational culture. On the other hand, in the long run, women are often forced to choose part-time precisely because of the difficulty in balancing career and private life (Gregory 2021). size ranged from 7 to 48 for focus groups, 6 to 67 for interviews and was of 79 participants for qualitative analysis of open-ended questions of a survey.…”
Section: Work-life Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Parental deep involvement with precise planning starting from their secondary school indicated their high expectations for my participants to have a future career. They seized this opportunity to negotiate a temporary space to exercise their agency, but with constraints (Gregory 2020). Different degrees of dialogues led to a nonlinear career trajectory, and in some situations, a 'staggered' career.…”
Section: Culture Unboundmentioning
confidence: 99%
“…One of them is the biased attitude of male colleagues towards female colleagues (Alwis, 2020). Maternity paid leave attracts many female employees, but the later part is pathetic when they try to enter the job market again the stereotypes such as she cannot pay attention to work as they are divided between mother role and office employ (Gregory, 2020). After childbirth, it is difficult for females because she has to care for her newborn child and office timings are usually not flexible for female employees (Kaushiva, 2020).…”
Section: Descriptionmentioning
confidence: 99%